THE FORMATION OF THE MILITARY-ADMINISTRATIVE GOVERNANCE SYSTEM IN THE SAMARKAND REGION IN THE LATE 19th – EARLY 20th CENTURY - Bo’tayev J. Sh. (TARIXIY TADQIQOTLAR, 2026)
This article analyzes the formation of the military-administrative governance system introduced by the Russian Empire in the Samarkand region in the late nineteenth and early twentieth centuries. The study examines the establishment of the Samarkand region based on the 1886 “Regulation on the Administration of the Turkestan Territory” and explores the structure of governance at the levels of region, district (uezd), precinct, volost, as well as village and aul communities. In addition, the powers of district chiefs, precinct officers, and local administrative representatives, as well as the functioning of the electoral system and mechanisms of administrative control, are analyzed on the basis of archival documents and historical sources. The article demonstrates that under the colonial policy of the Russian Empire, the military-administrative governance system served as an important instrument for strengthening political, social, and economic control over the region.